Factors Related to Outcome and Length of Hospital Stay for Elderly Patients with COVID-19 at Mataram University Hospital in 2020-2021 - Komang Pranayoga Prandhana Putra Nartha; Prima Belia Fathana; Rina Lestari (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Indonesia is one of the countries with the highest mortality rate for COVID-19 cases. The elderly group contributed the highest COVID-19 death outcome, which was 48.9% of the total COVID-19 death cases in Indonesia. This study aims to determine the factors related to outcome and length of stay of elderly patients with COVID-19 at the Mataram University Hospital in 2020-2021. This study is a cross-sectional study using the consecutive sampling method obtained from the medical records of elderly patients with confirmed COVID-19 that had met the inclusion and exclusion criteria at the Mataram University Hospital. Univariate and bivariate data analysis using chi-square test. The results showed that 66.7% of the elderly with death outcomes were aged 60-70 years, 77.8% were male, 88.9% had >1 comorbidity and 66.7% had a critical illness degree. Based on length of hospital stay, 53.3% of the elderly with length of hospital stay >14 days were >70 years old, 73.3% were male, 73.3% had >1 comorbidity, and 46.7% had moderate disease. Factors related to the outcome were comorbidities (p=0.015) and disease degree (p<0.001). Factors related to the length of hospital stay were age (p=0.049) and comorbidities (p=0.029). There is a significant relationship between comorbidities and disease severity with the outcome. There is a significant relationship between age and comorbidities with the length of hospital stay.